Managing Risk and Opportunity : The Governance of Strategic Risk-taking - Andersen, Torben Juul.; Garvey, Maxine L; Roggi, Oliviero (Oxford, United Kingdom : Oxford University Press, 2014)
This title looks at the critical demands imposed on directors and leaders when faced with corporate risks in turbulent global markets. It shows show why successful risk management outcomes require ethical governance principles and organisational structures that enhance effective risk-taking practices by all actors.
Includes bibliographical references and index.
oif 22/06/15
Loan
Keywords: Risk management; Corporate governance